Features of the management of educational institutions in the UK: theoretical and practical aspects (Acta Education, 2025)
The article is devoted to the study of the specifics of the management of educational institutions in the UK. This study was conducted to identify the features and uniqueness of the management system of educational institutions in the UK. For a full understanding of its functioning, it is necessary to consider both the theoretical foundations and practical aspects of implementation on the ground. Considerable attention is paid to the main trends and changes in the management of schools, colleges and universities in the UK. Also, the article analyzes the key models and theoretical concepts that underlie the educational policy of the UK